Poučevanje "evropske literature" prek zgodovine kritike - Sinopoli, Franca (Primerjalna književnost, 2006)
Teaching "European Literature" through the History of Criticism: The Concept of "Model Author" as the Starting Point. The starting point of the article is the intersection of identities formed as a consequence of relationships among different cultures. The author refers to some of the main 20th century representatives of literary criticism, based upon the concept of "model author/text", and considering some other concepts, and verifies their applicability to the didactics of comparative literature. This should enable appropriate understanding of European literature (territorially determined as well) and its relationship to different, not only European literatures and cultural identities.
Keywords: comparative literature; primerjalna književnost; evropske književnosti; literarni kanon; literarni vplivi